Prospek Pengembangan Usaha Pada UMK Pengupasan Daging Rajungan Di Sei Ladi Kota Tanjungpinang - Lasari, Yosi; Khairunnisa, Khairunnisa; Tetty, Tetty (MarIslands, 2021)
This study aimed to analyze the feasibility business of UMK Pengupasan Daging Rajungan. This research was in February-April 2021 in UMK Pengupasan Daging Rajungan Sei Ladi of Tanjungpinang city. The sampling method used is the purposive sampling method. The feasibility was analyzed using R/C ratio, B/C Ratio, BEP Volume, BEP Price, Payback Period, and NPV. Business development prospect in UMK Pengupasan Daging Rajungan will be identified using a SWOT analysis. The research result obtained profit for UMK Pengupasan Daging Rajungan, the R/C Ratio value is 2.45, B/C Ratio is 1,45, BEP Volume is 4.718.22 kg, BEP is Rp101.985, Payback Period is 1 year, 2 months 7 days, NPV is Rp5.713.143.210. UMK Pengupasan Daging Rajungan is profitable and feasible to be developed. Based on the identified SWOT analysis, UMK Pengupasan Daging Rajungan has 6 advantages in terms of capital, complete infrastructure, strategic location, carrying out fishing development, empowering marine products, and already having a business license. Weaknesses of UMK Pengupasan Daging Rajungan unstable crab supply and the absence of utilization of crab shell waste. Opportunities owned by UMK Pengupasan Daging Rajungan are a large market, the opportunity to expand their business, high market demand, and having regular customers. Meanwhile, the current threats are the lack of fishing gear, competitors, Pandemic Covid-19, and the used fishing gear that damages the crab habitats.